PERLUASAN MAKNA KATA YABAI SEBAGAI WAKAMONO NO KOTOBA - Maully Maulana Prawira (Sekolah Tinggi Bahasa Asing (STBA) Yapari-ABA Bandung, 2017)
There is a lot of information that contain meanings expansion. Especially Wakamono Kotoba, Japanese language used by young people contains semantic expansion. Such words are usually not included in the existing dictionaries, making the meanings of these words diflicult to be recognized. However,Wakamono Kotoba often cannot be recognized as onesemantic word by morphological analysis.Used Wakamono Kotoba limited to certain groups of young people (teens in the community).Wakamono Kotoba is mainly classified into two groups: one expresses or evokes emotion and another does not. However, this classificationis sometimes not so clear semantically. For example, the word Yabai originally means dangerous, but young generations use it to mean great. Yabai is a direct example where the original negative emotion is changed to a positive emotion in the usage of Wakamono Kotoba